Digitalization and civic participation in rural areas: A systematic review of scientific journals, 2010-2020; Digitalisierung und Beteiligung in ländlichenRäumen: Eine systematische Literaturschauwissenschaftlicher Zeitschriften, 2010-2020 - Veronika Stein; Christian Pentzold; Sarah Peter; Simone Sterly (Raumforschung und Raumordnung / Spatial Research and Planning, 2022)
The smart village is digitally networked and participatory. Its 'smartness', in other words, should be based on interaction between technological infrastructures and civic engagement. While this vision has inspired European policymaking and public discourse in recent years, understanding of the interaction between digitalization and civic participation in rural areas remains limited. In order to fill this gap, this paper offers a systematic review of journal contributions situated at the intersection of digitalization, participatory efforts and rural development. Overall, our study shows that digital rural development and its interplay with participation processes is still a niche concern in scientific journals. We find that articles focus primarily on projects seeking to increase broadband capacity. Second, they focus on the spatial characteristics of rural areas, where social relations and intermediaries play an important role. Third, they emphasize the integration of topdown measures with bottom-up initiatives. There is no single, dominant theoretical approach conceptualizing the intertwining of digitalization and civic participation processes in rural areas. It is evident that local social networks are strengthened and maintained through both analogue and digital formats. Furthermore, the literature provides evidence that sustainable forms of digital engagement are based on civil society initiatives that are supported and accompanied by administrative measures. – – Das smart village ist digital vernetzt und partizipativ. Seine angenommene smartness soll also auf der Verschränkung von technologischen Infrastrukturen und der Beteiligung der lokalen Bevölkerung beruhen. Doch obschon diese Vision in den letzten Jahren die europäische Politikgestaltung wie den öffentlichen Diskurs beflügelt hat, ist das Verständnis der Wechselwirkungen zwischen Digitalisierung und Partizipation in ländlichen Räumen noch begrenzt. Um diese Lücke zu schließen, stellt dieser Beitrag eine systematische Literaturschau zur Digitalisierung im Zusammenspiel mit Partizipation in ländlichen Räumen vor. Insgesamt wird dabei deutlich, dass die digitale Entwicklung im ländlichen Raum immer noch ein Nischenthema in wissenschaftlichen Zeitschriften ist. Ein zentraler Fokus lag in den einbezogenen Studien auf Projekten des Breitbandausbaus. Darüber hinaus wurden häufig die räumlich bedingten Merkmale ländlicher Gebiete diskutiert, in denen soziale Beziehungsgefüge und Intermediäre eine wichtige Rolle spielen. Schließlich wurde die Verschränkung von top-down-Maßnahmen mit bottom-up-Initiativen betont. Es fand sich kein dominanter theoretischer Ansatz, um das Ineinander von Digitalisierungs- und Partizipationsprozessen in ländlichen Räumen zu konzeptualisieren. Die Synopse unterstreicht die Wichtigkeit lokaler sozialer Netzwerke, die mittels analoger und digitaler Formate aufrechterhalten werden. Darüber hinaus liefert die Literatur Hinweise darauf, dass nachhaltige Formen digitalen Engagements auf zivilgesellschaftlichen Initiativen beruhen, die durch administrative Maßnahmen unterstützt und begleitet werden.
Keywords: 710; Participation; Civil Society; Digitalization; Literature Review; Rural Areas; Beteiligung; Zivilgesellschaft; Digitalisierung; Ländliche Räume; Literaturschau